A modified Fourier approach for analysis of nanofluid heat generation within a semi-circular enclosure subjected to MFD viscosity. (February 2020) - Dogonchi, A.S.; Waqas, M.; Seyyedi, Seyyed Masoud; Hashemi-Tilehnoee, M.; Ganji, D.D.
Abstract: In this study, the heat transfer behavior in a semi-circular cavity filled with Fe3 O4 -H2 O nanofluid is analyzed using the modified Fourier formula. MFD (magnetic field dependent) viscosity is considered for ferrofluid viscosity. The salient features elaborating transportation of heat namely the heat sink/source aspect is accounted. The control volume finite element method (CVFEM) is employed for numerical computations of the nonlinear system. The effects of different parameters such as Hartmann number, heat source/sink parameter, thermal relaxation parameter, Rayleigh number, nanoparticles volume fraction and shape factor on heat transfer and fluid flow properties are investigated. Based on the active parameters of the study, a correlation was obtained for the average Nusselt number. According to the results, the average Nusselt number is proportional to nanoparticles volume fraction, thermal relaxation factor, and Rayleigh number. The results also indicate that the magnetic field can be applied as a regulatory factor to the system. It is also concluded that the spherical shape nanoparticles provide lesser heat exchange while the platelet nanoparticles shape represents better heat exchange.